Geneologi Pengetahuan Pelaku Usaha Batik Dalam Pemasaran Melalui Media Sosial di Desa Tanjungbumi Kabupaten Bangkalan - Anik Andriani; Achmad Syarifudin (Journal of Social, Culture, and Language, 2023)
Batik is an aspect of Indonesian culture, which is the identity of Indonesian culture. Batik is spread throughout the islands of Indonesia, one of which is in the Tanjungbumi district. The great potential of the village is an important aspect to continue to be developed. The location of this research is located in Tanjungbumi Village, Bangkalan Regency. Data collection methods were carried out through literature studies, field research in the form of observations and interviews. Data analysis used in this research uses qualitative descriptive data analysis. Through this descriptive analysis, the researcher provides an overview or description of the object of research that has been carried out. In today's modern era, it is very necessary to market batik through social media because marketing through social media can increase revenue and can introduce batik not only within the scope of the archipelago but also internationally. In social media marketing can be done with Facebook, Instagram, Whatapps, and Tiktok accounts. Marketing carried out by business actors through social media has not been evenly distributed, due to differences in social background in the form of age and educational background. Different knowledge and ways of thinking give rise to the geneology of power in it. The geneology of power plays with the concept of power is knowledge, knowledge is power, which means that knowledge can be used as power by someone. Business actors who market through social media can have broad power relations and have a wide market network so that they can market domestically and abroad. The existence of batik marketing through social media gives rise to the power relations that exist in it. Keyword: Batik, Social Media, Geneology, Power